Exploitation of Absolute qPCR to Estimate Lactobacillus and Bifidobacterium Count in Human Gut as Indicator of Diabetic Mellitus Complication - Al-Rawe, Ali Mohammed; Suleiman, Ahmed AbdulJabbar (Iraqi Journal of Science, 2020)
Diabetes mellitus is a form of metabolic disorder where patients are incapable to organize glucose metabolism. The most common types are Type I and Type II, constituting about 10% and 90% of cases, respectively. The cause of type I diabetes, which usually spreads in children and adolescents, is the disability of the endocrine system to produce insulin. On the other hand, The most common type of diabetes, type II diabetes, is often presented in adults. It is usually presented as a collection of insulin deficiency and insulin resistance. This work was done to estimate the count of microbiota in diabetics to find an appraoch for detection and follow-up treatment. The count of two types of bacteria Lactobacillus and Bifidobacterium was determined using qPCR based on the standard curve that was created from the serial decimal dilution of samples containing an unknown number of bacteria taken from probiotic capsules. The main results of this study show that the Lactobacillus count was affected by diabetes types, where a decrease was observed in the mean value in the case of diabetes type I group (32978.13) compared with the control group (610680.26). The mean value in diabetes type II was close to that of the control group (682199.27). While, the count of the Bifidobacterium showed a significant reduction in the mean value in both type I and type II diabetes groups (7521.70, 51880.82, respectively), compared with the control group (63405999.00).